The Possibilities for an Urban Community Action Plan and Collaborative Work Support for Slum Improvement: A Case Study in Jakarta - Yusuf Fadli; Riska Sarofah (Policy & Governance Review, 2021)
This study describes community development in the preparation for a community action plan for slum management in DKI Jakarta. The case study chosen for this research is the Akuarium village. The existence of slums is an inseparable part of the development of a city. The slum area contributes to several problems such as population density, building conditions, ventilation, sanitation, garbage, drainage, environmental roads, lighting and building layout. In an effort to overcome these problems, it is important to develop a community development concept that emphasizes the participation of the community through collaborative work between the government and citizens in the development process. The research that has been done has not touched on the substance of the problem faced by the urban poor and how the community plays a role in supporting the program. The purpose of this research is to find out how community-based development patterns can encourage collaborative work of each actor in structuring slum villages in DKI Jakarta. In this study, the method used is qualitative with in-depth interviews and data processing using the Nvivo 12+ application. The results showed that the principles of community development, including integrated development, participation, sustainable development, empowerment, and human rights, greatly influence the collaborative work of various stakeholders in planning an Akuarium development action plan.